Comparative assessment of the climatic comfort of Ukrainian regions for the development of recreation and tourism - Maksymenko , N. V.; Protasova, O. S. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2024)
Purpose. To study the climatic comfort of Ukrainian regions as a basis for further development of recreation and tourism. Research methodology. Comparison of climatic comfort is carried out according to the index of temperature and humidity and the index of wind efficiency with reasonable author’s adjustments in accordance with the natural conditions of Ukraine. Results. The study period covers 30 years: from 1991 to 2021. Materials from all regions of Ukraine and the Autonomous Republic of Crimea were used. It was found that for 7 months Ukraine is in the zone of uncomfortable weather (from January to April and from October to December). The discomfort is observed for 1-2 months longer in 8 regions: Rivne, Zhytomyr, Lviv, Ivano-Frankivsk, and Khmelnytsky (9 months from January to May and from September to December) and 8 months from January to April and from September to December in Vinnytsia, Chernihiv, and Sumy. A regularity was found that comfortable weather "migrates" from south to north from May to August. This phenomenon can be explained by the fact that during the transition period, negative subcomfort is observed in almost all regions of Ukraine, unlike the comfortable south. In June, the comfort "moves" to the Central region (Cherkasy, Kirovohrad regions), the Central-Western region (Khmelnytsky, Vinnytsia, Zhytomyr regions), the North-Eastern region (Chernihiv, Sumy, Poltava regions), the North-Western region (only Volyn region), and the South-Western region (only Chernivtsi region). In July, almost the entire territory of Ukraine has subcomfortable weather with positive indicators, and only 3 regions are comfortable (Rivne, Zhytomyr, Ivano-Frankivsk). Comfortable weather in August also "appears" in the Western region (Lviv, Ivano-Frankivsk, Rivne regions) and returns to Chernihiv, Zhytomyr, Khmelnytsky, and Volyn regions.In September, comfort "returns" to the south, as negative subcomfortable and uncomfortable weather prevails in Ukraine. Conclusions. The study has identified periods with comfortable weather for different regions of Ukraine, which can be used for tourism needs: planning excursion routes; creating strategies for the development of recreational activities in the region; creating newsletters and providing information on the "best" time for recreation; organizing seasonal tours to the regions of Ukraine.